Exposing medical students to various difficulty levels of simulated endotracheal intubations improves success rate: a randomised non-blinded trial. (19th January 2019) - Kazan, Roy; Giacalone, Marilù; Liu, Jiaru; Brogi, Etrusca; Cyr, Shantale; Hemmerling, Thomas M
Abstract : Objective: Simulation training of endotracheal intubation (ETI) has proven to be an effective training tool. We used an adjustable airway mannequin that allows the achievement of various difficulty levels of laryngoscopy to train inexperienced medical students. The purpose of this study was to evaluate the effect of training using this novel airway mannequin on ETI success rates of medical students. Methods: This was a randomised non-blinded trial conducted at the Steinberg Centre for Simulation and Interactive Learning. Twenty recruited medical students were randomly allocated to two different training groups. During training, the mixed training group was asked to perform successful intubations in three levels of difficulty; the standard training group was asked to perform the same number of successful intubations in one level of difficulty. After training, all participants were asked to perform intubations using both the adjustable airway mannequin and a standard mannequin. Success rates and airway surface area visualised were compared between the two groups. Results: Students in the mixed training group had a significantly higher success rate both in the adjustable airway mannequin (p=0.01) and in the standard mannequin (p=0.02). Students in the mixed group had 51%, 59% and 47% significantly more visual area surface than students in the standard group during standard and difficult setup of the adjustable airway mannequin and the standard airway mannequin, respectively. Conclusions: The use of an adjustable airway mannequin to train medical students leads to superior ETI success rates and better glottis visualisation.